2019
DOI: 10.3389/fimmu.2019.01249
|View full text |Cite
|
Sign up to set email alerts
|

ERdj5 in Innate Immune Cells Is a Crucial Factor for the Mucosal Adjuvanticity of Cholera Toxin

Abstract: Cholera toxin (CT) is one of most strong mucosal adjuvants, but it cannot be clinically used owing to its toxicity. The cytosolic A1 subunit of CT (CTA1) is the molecule responsible for its immunostimulatory activity, which increases the concentration of cyclic AMP and causes the induction of pro-inflammatory cytokines in innate immune cells. However, the importance of endoplasmic reticulum (ER) molecules involved in CTA1 retro-translocation to induce immune responses remained to be investigated. ERdj5 is an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…CTB is a nontoxic subunit that produces target cells blocking antibodies and is a potent mucosal immunostimulatory adjuvant that can incite potent mucosal and system immune responses [47]. Because of the strong adjuvanticity of CTB, it is applied in different peptide and DNA vaccines such as microbial and cancer [48,49]. In addition to playing a role as an immunostimulatory adjuvant, CTB is also a powerful protective antigen.…”
Section: Discussionmentioning
confidence: 99%
“…CTB is a nontoxic subunit that produces target cells blocking antibodies and is a potent mucosal immunostimulatory adjuvant that can incite potent mucosal and system immune responses [47]. Because of the strong adjuvanticity of CTB, it is applied in different peptide and DNA vaccines such as microbial and cancer [48,49]. In addition to playing a role as an immunostimulatory adjuvant, CTB is also a powerful protective antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The mucoadhesive delivery systems are quite varied, and their principle is to increase the retention time of antigens in the mucosa, interact with the epithelium of choice and increase the absorption and release of antigens. Delivery systems commonly used in the formulation of mucosal vaccines can be classified into two groups: particulate delivery systems for antigens and solutions (Kim et al, 2019). The first group consists of systems capable of partially protecting the antigen from enzymatic degradation in mucous secretions, involving the antigenic protein, thus making it less vulnerable to attacks by the local innate immune system.…”
Section: Mucous Adjuvants and Delivery Systemsmentioning
confidence: 99%
“…The first group consists of systems capable of partially protecting the antigen from enzymatic degradation in mucous secretions, involving the antigenic protein, thus making it less vulnerable to attacks by the local innate immune system. Examples are emulsions, liposomes, virosomes, microspheres, immunostimulant compounds (ISCOMs) and pseudo viruses or virus-like particles (VLPs) (Villanova & Oréfice, 2010;Kim et al, 2019). The second group of delivery systems encompasses solutions where the antigen is dissolved or suspended, such as eggs and gels.…”
Section: Mucous Adjuvants and Delivery Systemsmentioning
confidence: 99%
“…CTA1 is the subunit responsible for the immunomodulatory activity in conjunction with ERdj5 in the endoplasmic reticulum, which is the target for CT. In the absence of ERdj5, mice failed to produce inflammatory cytokines, indicating that CT action requires ERdj5 (183). Similarly, the calcium-binding protein S100A4 is required for efficient antigen presentation and enhanced activity of CT, as it is necessary for the humoral and cellular response (184).…”
Section: Mucosal Adjuvantsmentioning
confidence: 99%
“…Similarly, the calcium-binding protein S100A4 is required for efficient antigen presentation and enhanced activity of CT, as it is necessary for the humoral and cellular response (184). CT has been tested as an adjuvant for pertussis vaccine and preliminary data suggests that it substantially improves mucosal protection by augmenting IgA levels (183,185), and it has even been suggested that this adjuvant may be safe for use in humans (186,187). Some studies have revealed that conjugation of CT with pertussis toxoid added to the current acellular vaccine (188) or Fimbriae (Fim2) (189) are highly promising candidates to improve the generation of protective immunity from these vaccines.…”
Section: Mucosal Adjuvantsmentioning
confidence: 99%